A case of pulmonary tuberculosis diagnosed in a patient with manifestations of haemophagocytic lymphohistiocytosis. Issue 3 (29th March 2019) - Ohata, Shinya; Hara, Kenta; Arai, Takashi; Takayoshi, Tomofumi; Nishiyama, Katsuhito; Yasutomo, Yoshiro; Yokono, Koichi; Sugimoto, Takeshi
Abstract: An 80-year-old woman was admitted with continuous fever, hepatic dysfunction and cytopaenia. The presence of hepatosplenomegaly, hyperferritinaemia, hypofibrinogenaemia and phagocytosis by macrophages in the bone marrow was consistent with a diagnosis of haemophagocytic lymphohistiocytosis (HLH). We suspected that HLH was induced by pre-existing tuberculosis, and antitubercular agents were started. Positive nucleic acid amplification and sputum culture for Mycobacterium tuberculosis resulted in a diagnosis of pulmonary tuberculosis. The patient improved with three months of treatment. In this patient, manifestations of HLH preceded those of pulmonary tuberculosis. A diagnosis of HLH should increase suspicion of disseminated tuberculosis and thus contribute to early detection.